Ответы и объяснения

2014-01-15T13:38:44+04:00
1. cosx-2=0
cosx=2
x=+-arccos2+2n*pi, где n пренадлежит Z

2.cos2x=-/3:2
2x = +-(pi-pi/6) + 2n*pi, где n пренадлежит Z
2x = +-5pi/6 + 2n*pi, где n пренадлежит Z
x= +-5pi/12 + n*pi, где n пренадлежит Z

3. 2sinx+/2=0
sinx = -/2:2
x=(-1)^n+1 * pi/4 + n*pi, где n пренадлежит Z

4. sin3x = 0
3x = n*pi, где n пренадлежит Z
x=n*pi/3, где n пренадлежит Z

5. 3tg4x-/3=0
3tg4x=/3
tg4x=/3:3
4x = pi/6 + n*pi, где n пренадлежит Z
x = pi/24 + n*pi/4, где n пренадлежит Z